A Genosensor for Sickle Cell Anemia Trait Determination. Issue 3 (28th October 2016) - Brazaca, Laís C.; Bramorski, Camila B.; Cancino‐Bernardi, Juliana; Janegitz, Bruno C.; Zucolotto, Valtencir
Abstract: Sickle cell anemia (SCA) is a common recessive genetic condition in which patients produce an abnormal form of hemoglobin. The disease is common mainly among African individuals and in parts of the continent up to 40 % of the population presents its genetic trait. Currently, disease diagnosis and trait determination are performed using polymerase chain reaction, liquid chromatography and electrophoresis. Although these methods present high sensitivity and are well established, they are costly and require specialized equipment to be performed. We developed an electrochemical genosensor for simple and low cost SCA trait determination. The device was based on the immobilization of single DNA strands containing the disease related mutation on gold platforms using the self‐assembled monolayers technique. The determination of SCA trait was then performed using electrochemical impedance spectroscopy. The genosensor displayed a wide linear range (0.01 to 7.5 μmol L −1, R 2 =0.979), with a detection limit of 7.0 nmol L −1 . Furthermore, the device was able to distinguish between DNA sequences containing or not the mutation (target and non‐target sequences) with precision and great reproducibility (10.4 %, n=3). It is expected that such sensor increases the number of SCA trait determination, promoting early diagnosis and genetically counseling. Abstract :